Cis-Pt I2(NH3)2: a reappraisal1. Issue 33 (7th September 2015) - Marzo, Tiziano; Pillozzi, Serena; Hrabina, Ondrej; Kasparkova, Jana; Brabec, Viktor; Arcangeli, Annarosa; Bartoli, Gianluca; Severi, Mirko; Lunghi, Alessandro; Totti, Federico; Gabbiani, Chiara; Quiroga, Adóracion G.; et al.
<x xml:space="preserve">Abstract</x> cis-PtI2(NH3)2 is highly cytotoxic toward a few solid tumour cell lines, furthermore it is capable of overcoming resistance to cisplatin.